2017
DOI: 10.3390/en10030393
|View full text |Cite
|
Sign up to set email alerts
|

International Electronical Committee (IEC) 61850 Mapping with Constrained Application Protocol (CoAP) in Smart Grids Based European Telecommunications Standard Institute Machine-to-Machine (M2M) Environment

Abstract: Abstract:As power systems develop rapidly into smarter and more flexible configurations, so too must the communication technologies that support them. Machine-to-machine (M2M) communication in power systems enables information collection by combining sensors and communication protocols. In doing so, M2M technology supports communication between machines to improve power quality and protection coordination. When functioning in a "smart grid" environment, M2M has been labelled by the European Telecommunications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…MQTT is more successful in terms of energy efficiency. In another study comparing CoAP and MQTT protocol in transporting the same data [19], CoAP protocol was stated to be more efficient. In a study conducted in an environment with high network traffic, the MQTT protocol was reported to be more successful than CoAP, with a higher bandwith and lower latency [20].…”
Section: Related Workmentioning
confidence: 99%
“…MQTT is more successful in terms of energy efficiency. In another study comparing CoAP and MQTT protocol in transporting the same data [19], CoAP protocol was stated to be more efficient. In a study conducted in an environment with high network traffic, the MQTT protocol was reported to be more successful than CoAP, with a higher bandwith and lower latency [20].…”
Section: Related Workmentioning
confidence: 99%
“…While these proposals feature widely used technologies (HTTP and XMPP), they incur a high communication overhead due to the text-based nature of HTTP and the complexity and overhead of exchanging presence information within eXtensible Messaging and Presence Protocol (XMPP), as well as it being based on the rather verbose eXtensible Markup Langage (XML). Shin et al propose in [16] the first approach to use a protocol specifically created for IoT systems, CoAP. However, the authors map just a reduced set of functions and they do not follow a RESTful approach, as they use different resources for PUT and GET requests.…”
Section: A Iec 61850 Mappingsmentioning
confidence: 99%
“…Ref. [21] adopts the OPNET simulator configured to assess the use of Constrained Application Protocol (CoAP) in an IEC 61850-based SAS. The work in [22] targets Distributed Automation Systems (DAS) addressing the autonomous execution of distributed applications, enabling IEDs to handle dynamic topologies and establishing data flows between independent IEDs.…”
Section: Related Workmentioning
confidence: 99%